Insights on the interaction of alpha-synuclein and metals in the pathophysiology of Parkinson's disease. Issue 3 (11th March 2015) - Carboni, Eleonora; Lingor, Paul
<x xml:space="preserve">Abstract</x> The interaction of different metals with the Parkinson's disease-associated protein alpha-synuclein results in oxidative stress, protein aggregation and pathology progression.